Revisiting the Past, Laying the Ground for the Future: Echoes of the COVID-19 Pandemic in the History of Education in Brazil - Silva Rabelo, Rafaela (Encounters in Theory and History of Education / Rencontres en Théorie et Histoire de l'Éducation / Encuentros en Teoría e Historia de la Educación, 2024)
One of the effects of the COVID-19 pandemic worldwide was the interest of different segments of society in revisiting the impacts and measures adopted in previous pandemics. In Brazil, it was no different; much was discussed and published, for example, about education. In the first year of the pandemic, in 2020, with the suspension of in-person classes, Brazilian magazines and newspapers published articles exploring experiences in previous health crises. This article aims to identify whether and how the context of the COVID-19 pandemic has impacted recent discussions and research on the history of education in Brazil. Specifically, it intends to explore whether the health crisis triggered connections between the history of education and environmental issues. The study is based on an analysis conducted on Brazilian news websites and academic journals on the history of education.